1988
DOI: 10.1159/000217548
|View full text |Cite
|
Sign up to set email alerts
|

Attempts to Suppress Experimental Allergic Encephalomyelitis in Rats with Alpha Fetoprotein

Abstract: Rats of the Lewis strain were immunized with bovine basic myelin protein to develop experimental allergic encephalomyelitis. Neither human nor rat fetal sources of purified α-fetoprotein were able to significantly ameliorate the development of this dyscrasia. The plasma of pregnant rats at term was without effect. Immunization of pregnant rats was also accompanied by the usual course of development of typical encephalomyelitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…However, a history of sexual intercourse with more than one partner was only reported in 03.91% of the study participants in this study. A study by Tanturovski et al [ 20 ] in Macedonia found that the vast majority of patients belonging to both early- and late-stage presentation of cervical cancer reported having two or fewer lifetime sexual partners (80% and 75.32%, respectively). This discrepancy might be due to the fact that in a country like India, having sex outside marriage or before marriage is considered taboo, so participants may have not revealed the information regarding sexual partners.…”
Section: Discussionmentioning
confidence: 99%
“…However, a history of sexual intercourse with more than one partner was only reported in 03.91% of the study participants in this study. A study by Tanturovski et al [ 20 ] in Macedonia found that the vast majority of patients belonging to both early- and late-stage presentation of cervical cancer reported having two or fewer lifetime sexual partners (80% and 75.32%, respectively). This discrepancy might be due to the fact that in a country like India, having sex outside marriage or before marriage is considered taboo, so participants may have not revealed the information regarding sexual partners.…”
Section: Discussionmentioning
confidence: 99%